Connecting the Dots: Exploring Means-End Theory in the Context of Customer Decision-Making for Sustainable Practices in Hospitality - Muqtader, ZahraZaidi; Mahani, Mohammad Abdu Shakur (International Publications, 2025)
Understanding customer decision-making towards sustainable hospitality practises is crucial in today's environmentally sensitive society and this study examined means-end theory (MEC) to display how customers' decisions are influenced by product features and perceived outcomes and values as the study presented a Consumer Decision Map (CDM) using quantitative methods to reveal consumer behaviour’s main decision patterns. Consumers' environmental concerns and willingness to pay more for hotels with strong green initiatives are strongly correlated and this emphasised over the importance of MEC and social identity theory and how values influenced consumer decisions. Similarly, the study also shed light on how hotel type affects consumers' willingness to pay (WTP) for sustainability as the luxury and mid-priced hotel visitors are more likely to pay for green efforts, suggesting a sustainability-based market distinction. Further investigation established that attitudes towards sustainability, perceived costs and benefits while perceived behavioural control are key to sustainable consumer behaviour (SCB) among luxury hotel customers under which the study focused over the need to expand the means-end theory (MEC) to fully understand SCB in the context of perceived costs and rewards. These results indicated major consequences for marketers and politicians under which effective communication and branding tactics that match consumers' beliefs and goals are crucial while the marketers would use CDM data to emphasize the link between sustainability and customer well-being, increasing green project acceptability and these data would also help policymakers create targeted policies to encourage sustainable hospitality practices. In this manner the research exposed the complex relationship between consumer values, hospitality decision-making and environmental measures while it linked means-end philosophy, customer behaviour and environmental concerns to create a more sustainable hospitality future.